Analysis of Determinants of Gen Z Employee Performance - Salman Farisi; Iskandar Muda (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study aims to determine the effect of self-efficacy, training and work environment on the performance of Gen Z employees at PT. Wahana Putra Yudha Pematang Siantar City both partially and simultaneously. This research approach is associative. Partially there is a positive and significant influence between self-efficacy on the performance of Gen Z employees at PT. Wahana Putra Yudha Pematang Siantar City. Partially there is a positive and significant influence between training on the performance of Gen Z employees at PT. Wahana Putra Yudha Pematang Siantar City. Partially there is a positive and significant influence between the work environment on the performance of Gen Z employees at PT. Wahana Putra Yudha Pematang Siantar City. Simultaneously there is a significant positive influence between self-efficacy, training and work environment on the performance of Gen Z employees at PT. Wahana Putra Yudha Pematang Siantar City.